Hubungan Pengetahuan Ibu Dengan Kelengkapan Imunisasi Lanjutan Dpt-Hb-Hib Dan Campak Rubela Pada Baduta Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2026 - Feny Triyany; Ravika Ramlis; Hengki Tranado (Jurnal Multidisiplin Dehasen (MUDE), 2026)
In 2024, the DPT-HB-Hib booster immunization coverage was 75.88% and the Measles/MR2 booster immunization coverage was 81.62%, with 76% of children receiving complete booster immunizations. Compared to the government's target of 100% booster immunization coverage for children under five, this achievement remains relatively low, falling short of the national target. The purpose of this study was to examine the relationship between maternal knowledge and the completeness of DPT-HB-Hib and Measles-Rubella booster immunizations among children under five in the Jembatan Kecil Community Health Center (Puskesmas) working area in Bengkulu City in 2026. The research method used was descriptive research with a cross-sectional approach. The sampling technique used purposive sampling with a population of 380 toddlers calculated using the Slovin formula, resulting in a sample size of 80 toddlers in the Jembatan Kecil Community Health Center Work Area, Bengkulu City, in 2026. Univariate analysis results showed that almost half of the respondents (45%) had sufficient knowledge, and the majority (63.7%) had completed the DPT-HB-Hib booster immunization. Bivariate analysis results showed a relationship between maternal knowledge and the completeness of the DPT-HB-Hib booster immunization and measles-rubella booster immunization in toddlers, with a p-value of 0.000. It can be concluded that maternal knowledge is associated with the completeness of the DPT-HB-Hib booster immunization and measles-rubella booster immunization in toddlers in the Jembatan Kecil Community Health Center Work Area, Bengkulu City, in 2026. The results of this study are expected to improve education and monitoring of booster immunizations to optimize DPT-HB-Hib and measles-rubella booster immunization coverage in toddlers.